Does Governance Facilitate Foreign Direct Investment in Developing Countries? - Hossain, Md. Shakib; Rahman, Md. Ziaur (International Journal of Economics and Financial Issues, 2017)
Using panel data analysis, it is an attempt to estimates the significance of governance on foreign direct investment for a sample of 80 developing countries from 1998 to 2014. For exploring the relationship, the paper has used the Kaufmann et al. (2003) interpretation concerning the governance. Generalized least square (GLS), feasible GLS (FGLS), pooled OLS, random effect, fixed effect, poisson regression, prais-winsten, generalized method of movement (GMM) and generalized estimating equation (GEE) method are utilizing for estimates the importance of governance for facilitating foreign direct investment. According to the OLS method ,for the governance variables the coefficient implies that a one standard deviation improvement in voice and accountability, political stability and absence of violence, government effectiveness, regulatory qualities, rules of law and control of corruption increases FDI by 29.4%, 29.2%, 28.6%, 20.5%, 23.1% and 23.6% respectively. Keywords: governance, foreign direct investment, generalized least square, generalized estimating equation JEL Classifications: C55, E22, G34